Rapid-onset methimazole-induced lupus in a pediatric patient with Graves’ disease: a case report and review of the literature - Deeb, Nouraldeen; Deeb, Salahaldeen; Badawi, Mohammad; Alfrookh, Mohammad; Douden, Bashar; Atawnah, Saed I. (Frontiers in Pediatrics, 2025)
Graves’ disease (GD) is the leading cause of autoimmune hyperthyroidism, though pediatric cases are uncommon. Methimazole (MMI) is the first-line therapy; however, drug-induced lupus erythematosus (DILE) secondary to MMI is rare and may be overlooked. We report the case of a 16-year-old girl with newly diagnosed GD who developed inflammatory polyarthritis, a diffuse pruritic maculopapular rash, and alopecia within 1 week of starting MMI (10 mg/day). Laboratory evaluation showed positive antinuclear antibodies and anti-histone antibodies, reduced complement C3 and low-normal C4, and negative anti-double-stranded DNA and extractable nuclear antigen antibodies; urinalysis was normal. MMI was discontinued and oral prednisone (20 mg/day) initiated, resulting in marked improvement within 1 week and complete symptom resolution by days 10–14. This presentation is notable for the unusually rapid onset of MMI-associated DILE in an adolescent and the presence of alopecia, a feature more typical of idiopathic systemic lupus erythematosus (SLE) than classic DILE. The case underscores the importance of maintaining a high index of suspicion for DILE shortly after antithyroid drug initiation, carefully differentiating it from idiopathic SLE using serology and clinical course, and promptly withdrawing the offending agent. Early recognition and short courses of corticosteroids can lead to rapid and complete recovery, while avoiding unnecessary investigations or prolonged morbidity.